Development of Dress Characters at MTI Khazinatul Asrar - Desi Desi; Umar Saleh; Weni Desita (KIPS Institute, 2025)
Clothing is one of the basic needs of humans to be able to interact with others in society, clothing is a means of protection as well as a self-identity. The meaning of Muslim clothing can be interpreted as clothing for Muslim women that functions to cover the genitals as stipulated by Islamic teachings to cover it. The focus of this research is related to the Development of Moral Clothing at MTI Khazinatul Asrar. This research aims to find out and explain the Development of Moral Clothing. The purpose of this research is to find out how to dress at MTI Khazinatul Asrar. The data for this research was obtained using a descriptive qualitative method. The data collection techniques used were through interviews, observation and documentation. Based on the results of research at MTI Khazinatul Asrar and the discussion, it can be concluded that clothing is one of the natural needs of humans to be able to interact with others in society, clothing is a means of protection as well as a self-identity. The meaning of Muslim clothing can be interpreted as clothing for Muslim women that functions to cover the genitals as stipulated by Islamic teachings to cover it, for the benefit and good of the woman herself and the society in which she lives. Besides covering the private parts, clothing also serves as protection to protect the body. Clothing also serves as jewelry, enhancing the wearer's beauty.